2017
DOI: 10.1016/j.carbon.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Carbon molecular sieve structure development and membrane performance relationships

Abstract: Characterization techniques beyond microscopy, scattering and spectroscopy approaches are needed to understand and improve sub-angstrom discrimination between penetrants in carbon molecular sieve (CMS) membranes. Here we use a method based on molecular scale gas diffusion probes to understand relevant membrane properties at the required level of detail. We further use this method to consider hypotheses about the evolution of structure responsible for fundamental properties of CMS materials derived from a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
149
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 47 publications
3
149
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15] Optimizing the permeability and selectivity of CMS membranes by tailoring precursors and/or optimizing pyrolysis conditions are accepted approaches. [19,20] These studies led to ad ramatically increased H 2 -vs.-hydrocarbon selectivity.W erefer to this phenomenon as hyperaging,and it is particularly relevant to important cracked-gas cleanup applications for large energy savings.T he hyperaging technique allows pore-size tuning to enhance the selectivity of specific gas pairs.U nlike conventional anti-aging efforts we have explored, hyperaging purposely accelerates the selective aging of CMS membranes,thereby creating CMS hollow fiber membranes with much higher performance for H 2 separation. [19,20] These studies led to ad ramatically increased H 2 -vs.-hydrocarbon selectivity.W erefer to this phenomenon as hyperaging,and it is particularly relevant to important cracked-gas cleanup applications for large energy savings.T he hyperaging technique allows pore-size tuning to enhance the selectivity of specific gas pairs.U nlike conventional anti-aging efforts we have explored, hyperaging purposely accelerates the selective aging of CMS membranes,thereby creating CMS hollow fiber membranes with much higher performance for H 2 separation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14][15] Optimizing the permeability and selectivity of CMS membranes by tailoring precursors and/or optimizing pyrolysis conditions are accepted approaches. [19,20] These studies led to ad ramatically increased H 2 -vs.-hydrocarbon selectivity.W erefer to this phenomenon as hyperaging,and it is particularly relevant to important cracked-gas cleanup applications for large energy savings.T he hyperaging technique allows pore-size tuning to enhance the selectivity of specific gas pairs.U nlike conventional anti-aging efforts we have explored, hyperaging purposely accelerates the selective aging of CMS membranes,thereby creating CMS hollow fiber membranes with much higher performance for H 2 separation. [19,20] These studies led to ad ramatically increased H 2 -vs.-hydrocarbon selectivity.W erefer to this phenomenon as hyperaging,and it is particularly relevant to important cracked-gas cleanup applications for large energy savings.T he hyperaging technique allows pore-size tuning to enhance the selectivity of specific gas pairs.U nlike conventional anti-aging efforts we have explored, hyperaging purposely accelerates the selective aging of CMS membranes,thereby creating CMS hollow fiber membranes with much higher performance for H 2 separation.…”
mentioning
confidence: 99%
“…[21] TheC MS pore morphology includes micropores (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) between the stacks of sheets and smaller ultramicropores (< 7 )within the individual sheets (Supporting Information, Figure S1). [21] TheC MS pore morphology includes micropores (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) between the stacks of sheets and smaller ultramicropores (< 7 )within the individual sheets (Supporting Information, Figure S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the well‐defined pore size distribution that contributes to the molecular sieving mechanism during the gas transport. Although significant research works have been reported as carbon membranes' invention, the need to improve the gas separation properties of these membranes remains tremendously important if they are to become viable for real applications . However, pyrolysis conditions are the main factors that affect both the membrane structure and gas permeation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant research works have been reported as carbon membranes' invention, the need to improve the gas separation properties of these membranes remains tremendously important if they are to become viable for real applications. 13 However, pyrolysis conditions are the main factors that affect both the membrane structure and gas permeation properties. To this end, as far as the carbon membranes are concerned, the study on pyrolysis atmosphere and thermal soak time is one of the milestones for researchers who are working in this field.…”
Section: Introductionmentioning
confidence: 99%